2020
DOI: 10.1097/icl.0000000000000669
|View full text |Cite
|
Sign up to set email alerts
|

A 5-Year Review of Acanthamoeba Keratitis Related to Wearing Contact Lenses in Korea

Abstract: Purpose: To investigate the presentation, clinical characteristics, and outcomes of Acanthamoeba keratitis (AK) in Busan, South Korea, over a 5-year period. Methods: This retrospective study involved a review of the medical records of 16 patients (19 eyes in total) who were diagnosed with AK, related to wearing contact lenses, at the tertiary hospital, Pusan National University Hospital at Busan City, from December 2013 to December 2018. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…A finding that may be attributed to the higher prevalence of CL wear among them. 1,21 Similar to other studies, 22,23 CL wear with bad hygiene was the most common risk factor of AK in our series. Based on the rural nature of the community where our study was performed, trauma by organic material was recorded as the second most common risk factor of AK due to prevalence of agricultural activities among the population.…”
Section: Discussionsupporting
confidence: 91%
“…A finding that may be attributed to the higher prevalence of CL wear among them. 1,21 Similar to other studies, 22,23 CL wear with bad hygiene was the most common risk factor of AK in our series. Based on the rural nature of the community where our study was performed, trauma by organic material was recorded as the second most common risk factor of AK due to prevalence of agricultural activities among the population.…”
Section: Discussionsupporting
confidence: 91%
“…11 It has been demonstrated that Acanthamoeba infections are commonly polymicrobial, 12 and we believe this was a case of coinfection with both Tsukamurella and Acanthamoeba. Contact lens use is the most common risk factor for Acanthamoeba, 12,13 which was a risk factor for our patient, and it may also be a risk factor for Tsukamurella infection. Whether there is a specific association between Tsukamurella and Acanthamoeba infections remains to be elucidated.…”
Section: Discussionmentioning
confidence: 70%
“…While the trophozoite form is much more easily eliminated, the cystic form is often difficult to target and eliminate [77][78][79]. Early recognition and prompt diagnosis can be critical in AK treatment, preventing deeper layers of the cornea from being affected [12,[80][81][82]. Treatment for AK typically consists of antimicrobial agents, including biguanides, diamidines, antiseptics, antiparasitics, antibiotics, and antifungal agents.…”
Section: Treatmentmentioning
confidence: 99%